Designing and Planning Tourism Park withEnvironment and Quality Vision andInformationTechnology-Based (Case Study: Natural TourismPark Raman Dam) - Fritz A. Nuzir; Agus Sukoco; Alex T (International Conference on Engineering and Technology Development (ICETD), 2012)
At present, the role of tourism ranked as the largest industryinIndonesiaeven in the worldand is aneconomicsectorthat has avery rapid growthand potentialjobsprovider. One ofa growingtourismsectorinIndonesiais anatural tourist attractions,Raman Damas one of thenaturaltourism potential ofits existencecannotbe developedandmanaged properly. Tourism Park (TW) Raman Damsite planning pays attention to severalaspects:Environmental Issues, The Past Metroandalignmentsofsurrounding communities.TW RamanDamconstruction, is expected tohave a visionto improvepeoples livesaround it. Apartfrom the economic, educationand participationconcerningtourismare expectedto formeithertothe surrounding community.InternationalStandardISO9001:2008whichspecifies requirements forquality managementsystemsforRamanDamParkthat need to becontinuallydemonstrated its abilityto producegood servicetovisitorsand stakeholders, as well asenvironmentalmanagementsystems(EMS) ieISO14001:2004 standardisasofthe overall management systemwhich includesorganizationalstructure, planningactivities, responsibilities, implementation procedures,in terms ofthetourisminformationsystem, supported by e-tourism inasimple understandingcan be definedasacomputer-based systemthat providesinformationforseveral userswith similar needs.